PD-L1 regulates the development, maintenance, and function of induced regulatory T cells - Francisco, Loise M. (The Rockefeller University Press, 2009)
Both the programmed death (PD) 1–PD-ligand (PD-L) pathway and regulatory T (T reg) cells are instrumental to the maintenance of peripheral tolerance. We demonstrate that PD-L1 has a pivotal role in regulating induced T reg (iT reg) cell development and sustaining iT reg cell function. PD-L1(−/−) antigen-presenting cells minimally convert naive CD4 T cells to iT reg cells, showing the essential role of PD-L1 for iT reg cell induction. PD-L1–coated beads induce iT reg cells in vitro, indicating that PD-L1 itself regulates iT reg cell development. Furthermore, PD-L1 enhances and sustains Foxp3 expression and the suppressive function of iT reg cells. The obligatory role for PD-L1 in controlling iT reg cell development and function in vivo is illustrated by a marked reduction in iT reg cell conversion and rapid onset of a fatal inflammatory phenotype in PD-L1(−/−)PD-L2(−/−) Rag(−/−) recipients of naive CD4 T cells. PD-L1 iT reg cell development is mediated through the down-regulation of phospho-Akt, mTOR, S6, and ERK2 and concomitant with the up-regulation of PTEN, all key signaling molecules which are critical for iT reg cell development. Thus, PD-L1 can inhibit T cell responses by promoting both the induction and maintenance of iT reg cells. These studies define a novel mechanism for iT reg cell development and function, as well as a new strategy for controlling T reg cell plasticity.